Instability of ion-cyclotron waves in a 2D magnetospheric plasma with anisotropic temperature - Grishanov, N.I.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2007)
Dispersion equation is analyzed for field aligned ion-cyclotron waves in a two-dimensional (2D) magnetospheric plasma with circular magnetic field lines. The steady-state bi-Maxwellian distribution function is used to model the energetic protons in a hydrogen plasma at the geostationary orbit. As in the uniform magnetic field, the growth rate of the proton-cyclotron instability (PCI) in a 2D magnetospheric plasma is defined by the contribution of the energetic ions/protons to the imaginary part of the transverse permittivity elements. It is shown that the PCI growth rate in 2D axisymmetric magnetosphere can be significantly smaller than that is for the straight magnetic field case with the same macroscopic bulk parameters.